EMPIRE, COMMUNITY, AND CULTURE ON THE MIDDLE EUPHRATES. DURENES, PALMYRENES, VILLAGERS, AND SOLDIERS. - KAIZER, TED (Bulletin of the Institute of Classical Studies, 2017)
The focus of this paper is on the Middle Euphrates: Dura-Europos as its best-known urban settlement; a series of villages known mostly from two papyrological dossiers situated along the river; and the military stations on the Euphrates. The paper asks questions about the impact (or lack of it) of the culture of Palmyra on the region's communities. It is argued that Dura-Europos remains our best case study for social and religious life in a Near Eastern small town under the Roman empire, and that the only evidence that actually makes the town look potentially 'untypical' is the idiosyncratic source material related to its Palmyrene inhabitants. The paper also questions the traditional periodization of Dura's history and puts forward the hypothesis that at two points during the so-called 'Parthian phase' Palmyrenes took advantage of a power vacuum along the Middle Euphrates and became the dominant military factor in the region.